An Herbal Product Alleviates Bleomycin-Induced Pulmonary Fibrosis in Mice via Regulating NF-κB/TNF-α Signaling in Macrophages - Jing, Fei; Chen, Xi; Xue, Jingbo; Huang, Kai; Xing, Feng; Hu, Xudong; Peng, Yuan; Liu, Chenghai (Frontiers in Pharmacology, 2022)
Background and aim: Pro-inflammatory macrophages aggravated progress of pulmonary fibrosis both in patients and animal models. FZHY formula, a Chinese herbal product, is effective in treating pulmonary fibrosis in our previous study. But its action mechanism against PF relating to macrophage activation was unclear. This study was designed to evaluate the anti-fibrotic and anti-inflammatory roles of FZHY in pulmonary fibrosis and to elucidate the potential mechanisms. Methods: Network pharmacology was employed to identify the interrelationships among compounds of FZHY, potential targets and putative pathways on anti- pulmonary fibrosis. According to the data of bioinformatics analysis, the key pharmacological target for FZHY against PF was screened. The network pharmacological prediction was validated by a series of experimental assays, including CCK8, western blot and immunofluorescence staining. Then molecular mechanism of FZHY on relating to the predictive target were studied in bleomycin induced pulmonary fibrosis in mice with methylprednisolone as a positive control, and in LPS stimulated cultured macrophages in culture, respectively. Results: The network pharmacology analysis reveal that a total of 12 FZHY–PF crossover proteins were filtered into a protein-protein interaction network complex and designated as the potential targets of FZHY against pulmonary fibrosis, while TNF-α signal pathway ranked at the top. FZHY and methylprednisolone could attenuate the lung fibrosis and decrease pulmonary TNF-α expression in bleomycin induced fibrotic mice, without difference between two treatments. While TNF-α was mainly originated from macrophages identified by double fluorescent staining of TNF-α and F4/80. LPS stimulated cultured macrophage polarization and activation demonstrated by the enhance contents of TNF-α and iNOS but decreased level of Arg-1. FZHY could alleviate the LPS stimulated macrophage polarization and activation demonstrated by decreasing TNF-α and iNOS and increasing Arg-1. In particular, FZHY could significantly reduce the production of p65 and the nuclear translocation of phosphorylated p65. Conclusion: Fuzheng Huayu formula has a good effect against pulmonary fibrosis induced by bleomycin in mice, whose action mechanism was associated with down-regulation of NF-κB /TNF-α signaling pathway in pro-inflammatory macrophages. These findings provided an important strategy for developing new agents against lung fibrosis and accelerated FZHY product application on patients with lung fibrosis.